EVALUASI PENETAPAN KAWASAN ANDALAN: STUDI EMPIRIS DI KALIMANTAN SELATAN 1993-1999 - Aswandi, Hairul M.; Kuncoro, Mudrajad (Journal of Indonesian Economy and Business, 2002)
This paper attempts to evaluate government policy to classify a region as a key region (kawasan andalan) with special reference to South Kalimantan province. Using location quotient and logistic regression, we showed that the policy designed and based merely on regional income per capita and key subsector. The policy seems, to ignore the growth of regional income and regional specialisation. Our analysis also suggests that regional classification based on Klassen Typology is a better alternative than that of the ad-hoc âkey regionâ.Â Key words: kawasan andalan, LQ, logistic regression, Klassen Typology